Curating research data: the potential roles of libraries and information professionals. Issue 2 (2014) - ,; ,
Abstract : Purpose – A key issue in the literature about research libraries concerns their potential role in managing research data. The aim of this paper is to study the arguments for and against associating this task with libraries and the impact such an association would have on information professionals, and consider the competitors to libraries in this field.Design/methodology/approach – This paper considers the nature of data and discusses data typologies, the kinds of data contained within databases and the implications of criticisms of the data‐information‐knowledge (DIK) hierarchy. It outlines the many competing agencies in the data curation field and describes their relationships to different kinds of data.Findings – Many data are organically connected to the activities of large, domain‐specific organizations; as such, it might be difficult for research libraries to assume a leadership role in curating data. It seems more likely that the qualifications of information professionals will come to be needed in such organizations and that the functions of research libraries will shift toward giving greater prevalence to their role as specialists in scholarly communication. In some cases, however, research libraries may be the best place to select, keep, organize and use research data. To prepare for this task, research libraries should be actively involved in domain‐specific analytic studies of their respective domains.Originality/value – This paper offers a theoretical analysis and clarification of the problems of data curating from the perspective of research libraries.